Endocrine changes in sows in response to altered suckling and boar exposure - Newton, E.A.; Stevenson, Jeffrey S.; Minton, J. Ernest; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighteen sows were treated as follows: 1) 10 multiparous and four primiparous sows were separated from their litters for 6 hr/day and exposed to a mature boar for 1 hr/day during the last 8 days of lactation, and 2) four sows (two multiparous and two primiparous) served as untreated controls during lactation. Blood was collected from sows during treatment and after weaning, and various hormones were measured. Altered suckling induced higher concentrations of luteinizing hormone (LH) that caused multiparous sows to show estrus (10/10) during lactation. Younger treated sows had similar increases in LH, but had higher follicle-stimulating hormone (FSH) and no increase in estradiol during treatment as observed in older sows, suggesting a lack of available follicles to be stimulated by the changing LH secretion. Treated sows also had increased cortisol on the first day and increased progesterone on the second day of treatment compared with controls. No differences were observed for concentrations of insulin and thyroxine between treatment groups. Similar hormonal changes occurred in control sows after weaning as in treated sows that showed estrus during lactation. Altered suckling and weaning appear to stimulate similar changes in hormonal secretion before estrus.
Keywords: Swine; Endocrine; Sows; Boars